DISEASE STRUCTURE AND TREATMENT RESULTS OF PATIENTS AT THE DEPARTMENT OF SPINAL TRAUMA AND ORTHOPEDICS, MILITARY CENTRAL HOSPITAL 108, FROM 2017 TO 2021 - Le Thi Que; Nguyen Thanh Tung; Dao Thi Thuy Ngoc; Duong Thi Thuy (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to describe the disease structure and the results of treatment of the inpatients at the Department of Spinal Trauma and Orthopedics, Military Central Hospital 108, from 2017 to 2021 Methods: Retrospective, cross-sectional descriptive study. Results: The majority of the patients were aged 16-59 (the rate from 2017 to 2021 was 63.8%; 58.91%; 54.84%; 53.49%; 54.1% respectively). The patients covered by health insurance accounted for a high proportion with an increasing trend (from 90.12% in 2017 to 97.06% in 2021). The rate of the patients undergoing surgical treatment in each year was higher than the rate of patients undergoing internal treatment; in five years the rate of the patients indicated for surgical treatment was 73.70%, and indicated for internal treatment was 26.30%. The annual rate of the patients indicated for special surgery and type 1 surgery was 96% and over; the highest rate was 98.30% (in 2020).The results of the treatment from 2017 to 2021: the rate of the patients recovering and reducing disease was 98.5%, 98.3%; 99.5%; 98.9%; 99.1% respectively. The mortality rate of the patients in 2017 and 2020 was ≤ 0.1%, especially, in 2018, 2019 and 2021 there were no deads.